Green Fleet Management Strategy and Operational Sustainability: A Stakeholder Analysis of Indonesian Shipping Company Decarbonization Readiness - Renta Novaliana Siahaan; Suhartini Suhartini; Marudut Bernadtua Simanjuntak (International Forum of Researchers and Lecturers, 2026)
Indonesian shipping companies face mounting pressure to align their fleet management strategies with the International Maritime Organization's 2023 Revised GHG Strategy, yet the organizational readiness and strategic capability through which these companies are actually responding to decarbonization imperatives remain empirically underexamined. This study investigates green fleet management strategy and operational sustainability readiness among Indonesian shipping companies through a qualitative stakeholder analysis involving fleet managers, Designated Persons Ashore, and maritime management graduates. Data were collected through semi-structured focus group discussions and interviews with twenty-four participants between April 2025 and April 2026. Thematic analysis, cross-group comparison, and narrative synthesis were applied. Findings reveal three dominant strategic orientations—compliance-reactive, compliance-proactive, and sustainability-integrated—distributed unevenly across company size and fleet type segments, with the majority of participants' companies occupying the compliance-reactive orientation. Inter-departmental coordination deficits and the absence of dedicated sustainability management functions within most company organizational structures constitute the primary organizational barriers to advancing toward sustainability-integrated fleet management. The study contributes a stakeholder-grounded typology of green fleet management strategic orientation within the Indonesian shipping sector and provides actionable recommendations for company governance reform and STIP Jakarta's maritime management curriculum development.